The Effect of Islamic Work Ethics and Islamic Organizational Culture on Employee Performance - Ahnaf Fadhlurrohman; Fuad Mas’ud (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of Islamic work ethics and Islamic organizational culture on employee performance. This study uses Islamic work ethics and Islamic organizational culture as independent variables, and employee performance as the dependent variable. Population target in this study were employees of Binama sharia cooperative in Semarang who had worked for more than one year and were permanent employees totaling 139 people. This study uses a non-probability method with the type of purposive sampling. Data obtained from questionnaires were processed and analyzed using the SPSS program. The data analysis method used is Multiple Regression Analysis. The classical assumption test is also carried out. Hypothesis testing is conducted by using F-test statistical testing, t-test, and coefficient of determination test by using a significance level of 5 percent. The results showed that Islamic work ethics and Islamic organizational culture had a positive effect on employee performance. The results showed Adjusted R-square of 0.804, indicating that the variables of Islamic work ethic and Islamic organizational culture can explain employee performance variables by 80.4 percent, while the remaining 19.6 percent is explained by other factors.